Propose New Framework For Network Performance Testing Strategy - Razak, Mohd Kamal Tarmizi (2017)
Performance evaluation is one of the main concerns in the communication system. In any communication implementation, to determine the performance factor of the network, a testing of end-to-end connection process flow is required. An effective and coordinated testing procedure plays an important role in evaluating the performance of the network. Therefore, this study proposes a testing framework which specifies the types of communication mediums and technologies, the evaluation criteria and tools to carry out the testing. The proposed testing scheme is used as a guideline to analyze and measure the performance of the real time network.